The Effect of Online Sacrificial Animal Donation Intentions using the Kitabisa.com Application (Case study there is a Muslim community in Indonesia) - Anisya Rahmadani; Anas Hidayat (Institute of Computer Science (IOCS), 2022)
Donation activities for sacrificial animal donations can be done through online media such as the Kitabisa.com application. This study aims to analyze the intention of donating sacrificial animals online using the Kitabisa.com application in Muslim communities in Indonesia. The parameters measured include perceptions of use, ease, trust, and religiosity. Quantitative research with a statistical approach. Primary data were collected using questionnaires in the goggle forms, which were then shared via social media. One hundred ninety people were sampled using purposive sampling. Data analysis using SmartPLS with a level of evidence of 95% (p<0.05). The results of the study obtained the intention of donating sacrificial animals online to the Muslim community in Indonesia using the application Kitabisa.com were not influenced by the perception of usefulness (p = 0.187) and trust (p = 0.400) while positively influenced by the perception of ease (p = 0.003) and religiosity (p = 0.001). Hence, service providers, Kitabisa.com need to increase the information related to the usefulness and trust of the Muslim community to increase the intention of donating sacrificial animals online.